Determinantes ambientais na constituição química e atividade antioxidante de óleos essenciais de Xylopia aromatica (Annonaceae) da savana de Roraima - Jansem Filho, Sebastião Salazar (Universidade Federal de Roraima, 2022)
The evaluation of the determining environmental factors for the composition and essential oils of antioxidant activity of leaves of Xylopia aromatica (Annonaceae) was performed with nine specimens of the species present in three areas of Roraima savannah for 12 months. The oils were obtained by hydrodistilation of 100 g of leaves for three hours and the yields determined. The chemical characterization was determined by gas chromatography mass spectrometry (GC-MS) and gas chromatography with flame ionization detector (GC-FID). The rain precipitation was obtained by the data provided by the National Institute of Meteorology - INMET, the temperature and insolation data were obtained in each collection. Analyses of texture and soil fertility were carried out by the Faculty of Agronomy Eliseu Maciel, Federal University of Pelotas. The highest oil yields were in CCA-4 (0.84%) and CCA-5 (0.81%) and the lowest in North-08 (0.11%) and North-09 (0.14%). The major compounds were: β-phellandrene (37.5% +/- 26.5) for all individuals except for Southern 1, CCA-4 and 5, bicyclogermacrene (15.9% +/- 11.0) in all individuals, viridiflorol (5.16% +/- 4.68) and the unique South-3 individuals, CCA-5, and Northern 7,8 and 9. the compound unidentified ni-39 (13 47% +/- 20.58) was introduced mainly for the South-1 individuals, CCA-4 and 5 and the South-2 individual. The compound unidentified ni-43 (4.40% +/- 7.39) presented exclusively on CCA-4 individuals and 5. It was possible to the identification of 27 novel compounds. The antioxidant activity was determined by the average of the three analyzes showing low efficiency even with 40 µg/mL. By the DPPH∙. the lowest IC50 was observed in CCA-6 (0.511 µg/mL). By the method β-carotene method/linoleic acid samples were inducers of oxidation. Through multivariate analysis (PCA) was possible to establish correlations between income, higher in dry periods, and composition of oils with environmental factors, so the two cluster composition data is not justified by the spatial variation or temporal, but the level individual indicates strong tendency of separation between individuals where South 1 CCA-4 and 5 differ due to the variability of the α-muurolol content and ni-32. The more acidic pH of soil associated with higher concentrations of aluminum and increased cation exchange capacity (CEC-effective) had higher correlations for yield.